2007
DOI: 10.3727/000000007783464795
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Adipose Tissue Formation Enhanced by Basic Fibroblast Growth Factor and a Mechanically Stable Environment

Abstract: Engineered adipose tissue can be used in plastic and reconstructive surgery to augment soft tissue lost due to mastectomy or lumpectomy. The three-dimensional space provided by a scaffold capable of withstanding in vivo compressive forces and neovascularization may promote engineered adipose tissue formation. The objective of this study was to determine whether voluminous adipose tissue can be engineered by combining a mechanically stable environment with basic fibroblast growth factor (bFGF). Mechanical suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…Few studies also indicate that sue substitutes using human adipose tissue-derived mesenchymal stromal cells (ASC) may offer a future altersuch in vitro preformed vascular-like structures (or prevascular structures) are able to connect to the host vessels native to these current treatments (1,4,7,8,11). However, limited survival of in vitro-engineered adipose tissue after implantation (21,23,27,31).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies also indicate that sue substitutes using human adipose tissue-derived mesenchymal stromal cells (ASC) may offer a future altersuch in vitro preformed vascular-like structures (or prevascular structures) are able to connect to the host vessels native to these current treatments (1,4,7,8,11). However, limited survival of in vitro-engineered adipose tissue after implantation (21,23,27,31).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, bFGF-elaborated adipose tissue pads are small (typically <10 mm in diameter). 10,17 As a scale-up, sheep preadipocytes in alginate hydrogel yielded volumetrically maintained adipose tissue with a diameter of *15 mm after in vivo implantation. 18 In the present work, transplanted human ASCs are capable of generating a 40-mm hybrid soft tissue graft with cell survival in a thin layer of cellular interface with the host, and with volumetric expansion attributable to a large acellular biomaterial core.…”
Section: Discussionmentioning
confidence: 99%
“…16 Human preadipocytes seeded in poly(L-lactic acid)-[PLLA]-reinforced polyglycolic acid (PGA) fibers yielded adipose tissue after in vivo implantation. 17 Autologous sheep preadipocytes seeded in alginate hydrogel with or without RGD modification, after in vivo implantation, generated volumetrically maintained adipose tissue, with RGDmodified alginate showing advantage for cell adhesion and proliferation. 18 Despite the above-mentioned progress in the area of adipose tissue engineering, several critical roadblocks remain, including interrelated issues of angiogenesis, scaleup, and the maintenance of anatomic shape and dimensions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are currently the main source of growth factors that promote wound healing. Numerous studies have shown that platelet-rich plasma (PRP) promoted early wound healing [7][8][9] and was effective at enhancing the treatment of diabetic ulcers [10]. PRP is a desirable autologous source to promote soft-tissue deposition in areas of depletion, and it is often used in oral, maxillofacial, and plastic surgery procedures.…”
Section: Introductionmentioning
confidence: 99%